Late-onset Pneumo-orbit and Orbital Compartment Syndrome After Blunt Maxillofacial Trauma - Basak, Hazan; Yücel, Levent; Beton, Süha (ENT Updates, 2021)
Orbital compartment syndrome (OCS) is an urgent condition which requires immediate treatment to avoid permanent vision loss. If the associated increased intraorbital pressure causes optical nerve and disc compression, emergency treatment to reduce the pressure is required. Here, we report the initially conservative management of a minimally displaced medial orbital fracture after blunt maxillofacial trauma and the late but sudden development of pneumo-orbit and OCS.